Study on the influence of the addition of iron ore waste in the properties of the Portland cement concrete - Nascimento, Diogo Wagmacker; Vieira, Geilma Lima; Teles, Claudia; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2023)
The extraction of iron ore in Brazil has a fundamental role in economic and social development, contributing to the livelihood of several families in a large part of the national territory. However, the mining industry encounters problems related to the management of its waste in order to reduce the impacts caused by the accumulation of waste from this activity. In order to minimize the environmental, social and economic impacts caused by the mining activity, this work proposes the use of iron ore tailings for the production of concrete. The waste used originates from the mining activity in the state of Minas Gerais, specifically in the tailings dam in Fundão, Mariana - MG. In the present study, concretes were made with a water/cement ratio of 0.45 and 0.60, with additions of 0%, 5%, 10% and 15% iron ore tailing (IOT). The influence of residue additions on the mechanical strength of concretes was evaluated with the tests of tensile strength by diametrical compression and resistance to axial compression. With regard to mechanical strength, the additions of 10% of RBMF, in concretes with respect to a / c = 0.45 and 0.60, presented better results in relation to their references.